1997
DOI: 10.1055/s-2007-973692
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Magnetic Resonance Imaging and Mental and Motor Function of Very Low Birth Weight Children at Six Years of Age

Abstract: In this follow-up study, 20 of a geographically based year cohort of 31 surviving non-disabled VLBW (birthweight < 1500 g) children were examined at six years of age. The aim of the study was to relate cerebral MRI findings to neuro-development in these non-disabled children at six years of age. All MRI scans were evaluated for myelination pattern, periventricular gliosis, ventricular dilation and cortical atrophy. The Peabody motor test and the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 5 publications
4
51
2
Order By: Relevance
“…In addition, executive processes might be involved in reduced productivity in performing the Block Design, Picture Arrangement and Picture Completion tests (Lezak, 1995). Indeed, based on the literature, we expected more impairment in both the VaD and sVaD group for the following of these tests: Block Design (Johnson, Head, Kim, Starr & Cotman, 1999;Skranes et al, 1997;Wallesch, Curio, Galazsky, Jost & Synowitz, 2001), Digit Symbol Substitution (Boone, Pontón, Gorsuch, González & Miller, 1998;Mahurin, Velligan & Miller, 1998;Peavy et al, 2001), Picture Arrangement (Deckel, 1999;Hasselbalch et al, 1992;Peavy et al, 2001), and Picture Completion (Mahieux et al, 1998;Skranes et al, 1997). Also, the Object Assembly test does reveal frontal processing (Peavy et al, 2001;Randolph et al, 1993) and might involve an executive component.…”
Section: Methodsmentioning
confidence: 86%
“…In addition, executive processes might be involved in reduced productivity in performing the Block Design, Picture Arrangement and Picture Completion tests (Lezak, 1995). Indeed, based on the literature, we expected more impairment in both the VaD and sVaD group for the following of these tests: Block Design (Johnson, Head, Kim, Starr & Cotman, 1999;Skranes et al, 1997;Wallesch, Curio, Galazsky, Jost & Synowitz, 2001), Digit Symbol Substitution (Boone, Pontón, Gorsuch, González & Miller, 1998;Mahurin, Velligan & Miller, 1998;Peavy et al, 2001), Picture Arrangement (Deckel, 1999;Hasselbalch et al, 1992;Peavy et al, 2001), and Picture Completion (Mahieux et al, 1998;Skranes et al, 1997). Also, the Object Assembly test does reveal frontal processing (Peavy et al, 2001;Randolph et al, 1993) and might involve an executive component.…”
Section: Methodsmentioning
confidence: 86%
“…Similar results have been found in other studies. Skranes et al (8) found no correlation between MRI abnormality and IQ in VLBW children without disability at 6 y of age, and Krageloh-Mann et al (9) found no difference in performance in intelligence tests in very preterm children, with and without MRI abnormalities. Stewart et al (10) and Rushe et al (11) reported the results of MRI brain scans and neuropsychological outcome at age 14 -15 y of a cohort of 75 participants who were born at Ͻ33 wk gestation; 55% of this group had structural brain abnormalities demonstrated on MRI brain scans, but those with abnormal MRI brain scans did not perform less well on any measure of cognitive function.…”
Section: Discussionmentioning
confidence: 98%
“…7 The impaired control of sensory motor skills may be linked to damage in both the corticospinal tract and the visual pathways. 22 Diffuse prenatal (i.e. perinatal infection leading to cytokine-mediated inflammatory processes) 23 and postnatal insults (i.e.…”
Section: Discussionmentioning
confidence: 99%